Considerations on the effects that core material machining has on an electrical machine's performance - Al-Timimy, A.; Vakil, Gaurang; Degano, Michele; Giangrande, Paolo; Gerada, Chris; Galea, Michael (IEEE, 2018)
An often-overlooked aspect during the development process of electrical machines, is the validity and accuracy of the machine material properties being used at the design stage. Designers usually consider the data provided by the materials supplier, which is measured on material in an unprocessed state. However, the fact that the machining processes required to produce the finished product (e.g. the stator core) can permanently vary the material properties is very often neglected. This paper therefore deals with and investigates the effects that such processes can have on the overall machine performance. To do this, three sets of material data, based on 1) the materials suppliers’ data, 2) materials data based on conventional characterization methods and 3) materials data based on test samples that include the manufacturing processes, are used to develop three versions of the same baseline machine. The results of these three machines are then compared and the resulting variations of the machine’s performance presented and described. The chosen baseline machine is a high performance and relatively high speed, aerospace, electrical machine. Special attention is focused on the efficiency maps of the machine as this aspect is highly dependent on the material properties that are the most sensitive to manufacturing processes such as the material’s anhysteretic BH curve and its specific core loss.